The Cassava Value Chain in Mozambique - Costa, Carlos; Delgado, Christopher (World Bank, Washington, DC, 2019)
Cassava is the principal starch in Mozambique, at 30 percent of calories. It can be stored unharvested up to 30 months, but fresh cassava lasts only 3 days once harvested. Most processing in Mozambique is artisanal, to eliminate cyanogenic glycosides in the 90 percent of production from pest resistant bitter varieties. Only 6 percent of production in 2011 was used commercially for non-food, two-thirds for feed and one-third for starch. Low levels of productivity for cassava compared to elsewhere and poor transportation are the main barriers to the development of a processing industry. Unit costs of production range from USD 0.09 to USD 0.30 U.S. cents per kg. Producers would need to achieve 15 tons/hectare to be commercially viable, compared to average yields between 5 and 9 tons/hectare in Mozambique. Actions recommended include: adoption of a "Master Plan "; time-limited subsidies for industrial High Quality Cassava Flour, ethanol, and starch; a network of service providers to operate in smallholder areas to deliver improved inputs and extension; promotion of farmers’ associations for better access to service providers; research on pest control in sweet varieties; greater availability of global market intelligence; capacity-building for processing; and introduction of legal norms to prevent processors from polluting.